Remanufatura e reparo de telas de dispositivos de cristal líquido: modelo de negócio voltado ao enquadramento junto a Política Nacional de Resíduos Sólidos. - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
Data of institutions linked to the government, indicate that Brazil loses about R$ 8 billion per year to fail to recycle their solid waste, in this context, this work goes on to add with the willing objectives, by creating a business model for managing an industry of Contract Manufacturer for TFT-LCD Displays and exploring Services Remanufacturing and repair of LCD-TFT displays. All these products are intended for intermediate goods industry and services with the prospect of Adding Value to Sustainable productive chain, supply chain, providing Income and Employment generation to groups and associations on separate collection of consumer electronics, revitalizing , in a strategic way the trade balance of semiconductors components, today unfavorable, in the Brazilian and Latin American market. The methodology used aims to provide a holistic approach of the product chain, with the aim of having a better understanding of all gains, risks, advantages and disadvantages, with the purpose of showing the viability and sustainability of the proposed business model. Was examined initially, legal, environmental, social and economic aspects of electronic waste; then is presented a business plan for a company Spin-off, which proposes to build a remanufacture and repair industry, from products collected at the end of the life cycle. Glass with the deposition of the active matrix - TFT (ITO), is an essential raw material for business, will be availed from LCD Displays collected. Operations and strategies of the Spin-off Company are discussed starting from a sustainable value model, where the sustainable value generation is the efficiency of business processes, automation, acquisition of machinery and equipment, the production process design, in good management practices, knowledge management and technological innovation through the construction and improvement of new machines inherent Remanufacturing and Repair process, thus ensuring a high level of reuse of this raw material/waste, providing reintegration as intermediate good in the product life cycle, bringing financial benefits for cooperatives, professionalization of the cooperative members, maximizing the number of product collected with low loss of raw materials / process waste salvageable besides development actions related to the social aspects of sustainable development in the context of the Triple Bottom Line.
Keywords: Eco Gestão; Gestão ambiental; Logística reversa; LCD Displays (telas de LCD); Resíduos Eletroeletrônicos; Triple Bottom Line; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO: GERÊNCIA DE PRODUÇÃO